“El origen de la obra de arte”: ¿un “oasis” en el pensamiento heideggeriano? - Belgrano, Mateo (2020)
“The Origin of the Work Of Art: an Oasis Amid the Heideggerian Thought?” In 1935 Martin Heidegger surprisingly delivered a lecture in Freiburg on the origin of the work of art. Why sis Heidegger give such a lecture? Why did s “art” appear as a decisive question that year? We only find brief mentions on this subject in his works prior to the essay on art. How to fit this apparent “oasis” in Heideggerian thought? Following the steps of William Richardson, Martin Heidegger’s work is usually divided into two great moments separated by what is known as the turn (Kehre). Where should we approach the work from? Should we understand his ideas from what he has worked on in Contributions to philosophy? Or should we enter “The origin of the work of art” from the works of the first Heidegger? These questions, of a methodological-interpretative nature, are those that we propose to answer throughout the work, seeking to defend the following hypothesis: “The origin of the work of art” is a “frontier” work between these two moments of Heidegger, which is why it requires a “round trip” approach between the first and the second Heidegger.